2021
DOI: 10.35762/aer.2021.43.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Biochar from Rice Husk as Efficient Biosorbent for Procion Red Removal from Aqueous Systems

Abstract: Numerous reports have elucidated the use of biochar (BC) to adsorb dyes from wastewater. However, its applicability for adsorbing Procion Red, which causes carcinogenic and mutagenic effects on aquatic life, has not been studied. In this work, biochar produced from rice husk in Sumatera, Indonesia was used as a biosorbent for Procion Red removal from aqueous systems. Rice husk-BC was characterised using X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, surface area specific analysis, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…It can be concluded that the methylene blue adsorption onto banana stem occurs in a monolayer on a homogeneous adsorbent surface. The same result has been reported by Palapa et al [44].…”
Section: ) Effect Of Initial Mb Concentration and Isotherm Studysupporting
confidence: 90%
“…It can be concluded that the methylene blue adsorption onto banana stem occurs in a monolayer on a homogeneous adsorbent surface. The same result has been reported by Palapa et al [44].…”
Section: ) Effect Of Initial Mb Concentration and Isotherm Studysupporting
confidence: 90%
“…The Langmuir isotherm model assumes that procion red adsorption occurs chemically and is monolayer at a limited number of specific sites. Meanwhile, the Freundlich isotherm model is utilized for multilayer chemical adsorption, which is characterized by a nonuniform distribution of adsorption heat and heterogeneous surface affinities (Palapa et al, 2021). Based on the data presented in Table 3, it is demonstrated that the Freundlich adsorption isotherm model is more appropriate for 3 displays the thermodynamic parameters for the adsorption of procion red on rice husk, including ΔH (enthalpy), ΔG (Gibbs free energy), and ΔS (entropy) (Georgin et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the RHB spectrum s most obvious point is at 1070 and 799 cm −1 , which corresponds to Si-O-Si or Si-O, demonstrating the high Si content of RHB [50]. Figure 3c shows the spectra of the LDH/RHB composite, revealing that the distinctive band at about 1359 cm −1 is linked to the stretching vibration mode of NO −3 [51,52]. Another prominent set of band shifts was noticed from 1070 to 1001 cm −1 and 799 to 750 cm −1 in the spectra of LDH/RHB composite, which symbolizes the stretching vibration of Si-O-Si or Si-O, but their intensity was significantly reduced compared to that obtained in Figure 3c.…”
Section: Fourier Transform Infrared Analysismentioning
confidence: 95%
“…A different equilibrium contact time, thus, was proposed for Cu 2+ and Pb 2+ for the optimal performance of the adsorption system. Due to the unavailability or saturation of the free active sites at the surface of the LDH/RHB adsorbent, no changes in the adsorption capacity or removal efficiency were Figure 3c shows the spectra of the LDH/RHB composite, revealing that the distinctive band at about 1359 cm −1 is linked to the stretching vibration mode of NO −3 [51,52]. Another prominent set of band shifts was noticed from 1070 to 1001 cm −1 and 799 to 750 cm −1 in the spectra of LDH/RHB composite, which symbolizes the stretching vibration of Si-O-Si or Si-O, but their intensity was significantly reduced compared to that obtained in Figure 3c.…”
Section: Estimation Of the Equilibrium Contact Time And Optimization ...mentioning
confidence: 99%